Satisfaction Level of Mobile Application Implementation Towards Passengers: an Analysis - B, Zirawani; Z.H, Fatimah; N.M.R, Syazwa (International Journal of Engineering and Technology, 2018)
Taxi is become one of the most popular public transportation, especially in urban area. People may choose their public transports due to the comfortability, speedy and the efficiency.Â The mobile application is introduced in the way to create an easiness of booking matters in improving their system and target passengers. This technology of mobile apps is supposedly made convenient to the people with the booking system, which are able to fulfil all the requirements as demand by passengers. However, many mobile apps especially for booking system, there are still weaknesses, here and there. There are traffics while peak and off-peak hour. The system is jammed, passengers could not book and worse than that is the taxiâ€™s driver could not respond at all. Therefore, this research is very important to define all the factors contribute to those matters, in the way to purpose the robust mobile booking system for public transportation. Together with that, the satisfaction level factors towards the passengerâ€™s satisfaction on taxi services apps are analysed and verified. The research survey of questionnaire was designed to gain the primary data of respondents and been analysed using ANOVA in SPSS software. Findings of this research, hopefully can direct any others companies suite to this situation for a better mobile apps development.Â Â